Zeus: A distributed timed model-checker based on Kronos - Braberman, V. (2002)
In this work we present Zeus, a Distributed Model-Checker that evolves from the tool Kronos [8] and that currently can handle backwards computation of TCTL-reachability properties [1] over timed-automata [2]. Zeus was developed following a software architecture centric approach. It introduces some interesting features such as a priori graph partitioning, a sophisticated machinery to reach optimum performance (communication piggybacking and delayed messaging) and dead-time utilization, where every processor uses time intervals of inactivity to perform auxiliary, time-consuming tasks that will later speed up the rest of the computation. Although some good results have been obtained, early experiments pinpointed the difficulties of getting speedups using a parallel asynchronous version. We also propose some paths to overcome those obstacles. We would like to thank Sergio Yovine for making Kronos libraries available to us. © 2002 Published by Elsevier Science B.V.